Facilitators and Barriers of Using Mobile for Patient Education - Raziyeh Ghafouri (Patient Safety and Quality Improvement Journal)
Introduction:Patient education is a dynamic and continuous process that starts from the moment of admitting the patient and continues after the discharge. The objective of such education is to empower patients to do self-care and improve their quality of lives. Different methods are available for education. This study was aimed to explore the Facilitators and barriers of remote education using mobile massaging applications. Materials and Methods: The study was conduct as a participatory action research. Participants were 70 nurses, 14 physicians, and 96 patients. Data was collect with interviews. Data analysis method was content analysis and the research process consisted of four phases of planning, implementing, observing, and reflecting. Results: The categories of the Facilitators of mobile learning from physicians, nurses, and patients’ viewpoints were “more accessibility, complete and comprehensive, and ease of virtual education.” Among the barriers were “large volume of content, out of date content that puzzles the users, invalidity of some references, and the risk of infection transmission through mobile phone.” The participants emphasized on the necessity of codifying content, updating educational resources, teaching the methods of using reliable references, and codifying guidelines of disinfecting mobile phones. Conclusion:Patient education through remote education in virtual space using massaging applications is an efficient, comprehensive, accessible, and economic method that also brings patients’ satisfaction. It is essential to use experts’ viewpoints to update the references. The patients need to be educated about the right way of disinfecting mobile devices and find reliable references.